Ipilimumab 10 mg/kg versus ipilimumab 3 mg/kg in patients with unresectable or metastatic melanoma: a randomised, double-blind, multicentre, phase 3 trial. Issue 5 (May 2017) - Ascierto, Paolo A; Del Vecchio, Michele; Robert, Caroline; Mackiewicz, Andrzej; Chiarion-Sileni, Vanna; Arance, Ana; Lebbé, Céleste; Bastholt, Lars; Hamid, Omid; Rutkowski, Piotr; McNeil, Catriona; Garbe, Claus; et al.
Summary: Background: A phase 2 trial suggested increased overall survival and increased incidence of treatment-related grade 3–4 adverse events with ipilimumab 10 mg/kg compared with ipilimumab 3 mg/kg in patients with advanced melanoma. We report a phase 3 trial comparing the benefit–risk profile of ipilimumab 10 mg/kg versus 3 mg/kg. Methods: This randomised, double-blind, multicentre, phase 3 trial was done in 87 centres in 21 countries worldwide. Patients with untreated or previously treated unresectable stage III or IV melanoma, without previous treatment with BRAF inhibitors or immune checkpoint inhibitors, were randomly assigned (1:1) with an interactive voice response system by the permuted block method using block size 4 to ipilimumab 10 mg/kg or 3 mg/kg, administered by intravenous infusion for 90 min every 3 weeks for four doses. Patients were stratified by metastasis stage, previous treatment for metastatic melanoma, and Eastern Cooperative Oncology Group performance status. The patients, investigators, and site staff were masked to treatment assignment. The primary endpoint was overall survival in the intention-to-treat population and safety was assessed in all patients who received at least one dose of study treatment. This study is completed and was registered withClinicalTrials.gov, numberNCT01515189 . Findings: Between Feb 29, and July 9, 2012, 727 patients were enrolled and randomly assigned to ipilimumab 10 mg/kg (365 patients; 364 treated) or ipilimumab 3 mg/kg (362 patients; all treated). Median follow-up was 14·5 months (IQR 4·6–42·3) for the ipilimumab 10 mg/kg group and 11·2 months (4·9–29·4) for the ipilimumab 3 mg/kg group. Median overall survival was 15·7 months (95% CI 11·6–17·8) for ipilimumab 10 mg/kg compared with 11·5 months (9·9–13·3) for ipilimumab 3 mg/kg (hazard ratio 0·84, 95% CI 0·70–0·99; p=0·04). The most common grade 3–4 treatment-related adverse events were diarrhoea (37 [10%] of 364 patients in the 10 mg/kg group vs 21 [6%] of 362 patients in the 3 mg/kg group), colitis (19 [5%] vs nine [2%]), increased alanine aminotransferase (12 [3%] vs two [1%]), and hypophysitis (ten [3%] vs seven [2%]). Treatment-related serious adverse events were reported in 133 (37%) patients in the 10 mg/kg group and 66 (18%) patients in the 3 mg/kg group; four (1%) versus two (<1%) patients died from treatment-related adverse events. Interpretation: In patients with advanced melanoma, ipilimumab 10 mg/kg resulted in significantly longer overall survival than did ipilimumab 3 mg/kg, but with increased treatment-related adverse events. Although the treatment landscape for advanced melanoma has changed since this study was initiated, the clinical use of ipilimumab in refractory patients with unmet medical needs could warrant further assessment. Funding: Bristol-Myers Squibb.